Too Risk Averse to Purchase Insurance? A Theoretical Glance at the Annuity Puzzle - Antoine Bommier; François Le Grand (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
This paper suggests a new explanation for the low level of annuitization, which is valid even if one assumes perfect markets. We show that, as soon there exists a positive bequest motive, sufficiently risk averse individuals should not purchase annuities. A model calibration accounting for temporal risk aversion generates a willingness-to-pay for annuities, which is significantly smaller than the one generated by a standard Yaari (1965) model. Moreover, the calibration predicts that riskless savings finances one third of consumption, in line with empirical findings.
Keywords: D11; D81; D91; 330; annuity puzzle; insurance demand; bequest; intergenerational transfers; temporal risk aversion; multiplicative preferences; Altersvorsorge; Sterblichkeit; Risikoaversion; Intertemporale Entscheidung; Rationalität; Unvollkommener Markt; Theorie